Cover Feature: An Iron Porphyrin Complex with Pendant Pyridine Substituents Facilitates Electrocatalytic CO2 Reduction via Second Coordination Sphere Effects (ChemCatChem 18/2021). Issue 18 (21st August 2021) - Ramuglia, Anthony R.; Budhija, Vishal; Ly, Khoa H.; Marquardt, Michael; Schwalbe, Matthias; Weidinger, Inez M.
Abstract : The Cover Feature shows an artist impression of the electrocatalytic reduction of CO2 by bispyridine‐bearing Fe porphyrin hangman complexes. In their Full Paper, A. R. Ramuglia et al. describe how this structural design achieves to permanently position metal cations in close vicinity to the Fe active site and thus allows for stabilisation of reaction intermediates, such as the high energy carboxylate intermediate, and hence accelerate the overall catalytic reaction. More information can be found in the Full Paper by A. R. Ramuglia et al.